#TITLE_ALTERNATIVE# - THOMAS ALBERTZ ( NIM 10205070) pembimbing : Prof. Dr. Eng. Zaki SuÃ‚Â’ud, FERMI
At the writing of this manuscript, there will be some discussion about things - things that relate to the fusion reaction, one of which is the method of magnetic confinement in the tokamak. This method is often used in scientific experiments in several developed and developing countries. And in the writing of this manuscript will discuss the equation grad- shapranov which is one equation that is used to determine the characteristics of magnetic flux in the tokamak. Here also will be given an explanation regarding the solution of these equations which consists of 6 coefficients are not known, but reduced to five unknown coefficients to simplify the calculation. And do not miss also will be given parameters - an important parameter in tokamak is useful to obtain the solution equation. From final solution of this equation will be simulated using Matlab program to obtain images of magnetic flux from one type of tokamak at the forefront of the world in ITER. The configuration of the ITER tokamak is obtained from several references that already exist. So that we can know what these things can affect the magnetic flux in the tokamak.